P491 Infectious risk of vedolizumab compared with other biological agents in the treatment of Inflammatory Bowel Disease. (27th May 2021) - Innocenti, T; Roselli, J; Lynch, E N; Apolito, P; Parisio, L; Bagnoli, S; Macrì, G; Rogai, F; Milani, S; Galli, A; Milla, M; Dragoni, G
Abstract: Background: Vedolizumab (VDZ) is a gut selective anti-α 4 β 7 integrin antibody for the treatment of Inflammatory Bowel Disease with a well-known optimal safety profile. We aimed to compare the risk of infections of VDZ with that of anti-TNF drugs and ustekinumab, in patients with both ulcerative colitis (UC) and Crohn's disease (CD). Methods: All CD and UC patients undergoing biological treatment at our centre between June 2013 and June 2020 were retrospectively included. All infectious complications were registered, considering both inpatient and outpatient events. A comparison of exposure-adjusted infection rate of vedolizumab with that of anti-TNF drugs and ustekinumab was carried out, with a specific focus on the rate of gut infections. All infection rates were expressed in events per patient-years (PYs). Results: The overall exposure-adjusted infection rate was 11.5/100 PYs. Detailed information about the infectious complications related to the different biologics is reported in Table 1 . The most common infections were respiratory tract infections, cutaneous infections, HSV infections/reactivations, and gut infections. The rate of serious infections was 1.3/100 PYs. Among the 85 patients who were on a VDZ therapy, 17 (3 CD and 14 UC, median age 64, IQR 31–68) suffered an infectious complication. The exposure-adjusted incidence rate for vedolizumab was 17.5/100 PYs, with CD patients having a lower infection risk compared with UC patients ( p = 0.035). Gut infections were observed in 3.0% of the whole patient population (1.5/100 PYs) and were more common in the VDZ group ( p = 0.0001). Conclusion: Our study confirms the good safety profile of vedolizumab. Among patients treated with vedolizumab, those with UC have a higher risk of developing infectious complications. Patients treated with vedolizumab have a higher risk of gut infections compared with patients treated with anti-TNF drugs or ustekinumab. Presumably, this could be due to the gut-selective mechanism of action of vedolizumab.